2020
DOI: 10.1177/1847979020947236
|View full text |Cite
|
Sign up to set email alerts
|

The impact of AMO-HR systems on proactive employee behavior: The mediating contribution of leader-member and team-member exchange

Abstract: The aim of this study is to examine the impact of AMO-HR Systems (i.e., ability-enhancing HR practices, motivation-enhancing HR practices and opportunity-enhancing HR practices) on proactive employee behavior through the effect of leader-member and team-member exchange. A questionnaire was developed based on prior related works to collect the required data from a sample of 230 employees from 13 small companies in the service industry in the Jordanian capital, Amman. The results showed that nine HR practices ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…All team members are accountable for the productive outcome in recurring meetings. This echoes on the proactive employee behaviour with a better leader-member and team-member exchange, as suggested by Al-Tit (2020). This study focuses on the leaderless team, and team-members' exchanges are exploring.…”
Section: Introductionmentioning
confidence: 89%
“…All team members are accountable for the productive outcome in recurring meetings. This echoes on the proactive employee behaviour with a better leader-member and team-member exchange, as suggested by Al-Tit (2020). This study focuses on the leaderless team, and team-members' exchanges are exploring.…”
Section: Introductionmentioning
confidence: 89%
“…Al-Tit et al [17] conducted a questionnaire survey of industrial companies and, based on the analysis of responses, concluded that employee pro-activity is a function of three categories of HR practices. First, the employee should be supported to improve their skills.…”
Section: Concepts and Basic Theoriesmentioning
confidence: 99%
“…Second, the employee should be motivated and given the opportunity to share knowledge. Third, employees should be encouraged to participate in problem-solving in the presence of the lead manager, in order to improve the quality of relationships and to recognize team members, their support and effective communication [17]. According to Henri [18], there are two ways in which creative employees can be stimulated in a company.…”
Section: Concepts and Basic Theoriesmentioning
confidence: 99%
“…Studies have agile employees improve the firm performance and ensure its competitiveness (Cai et al , 2018; Pitafi et al , 2018). Some studies have indicated that the nature of the work environment can influence employee proactiveness (Al-Tit, 2020; Caesens et al , 2016). Employees who are proactive goal oriented willingly create a new and different future by changing themselves and their environments (Parker et al , 2010).…”
Section: Introductionmentioning
confidence: 99%